Security as a tool for safeguarding artistic collections in private art galleries in Zimbabwe: a case of First Floor Art Gallery, Harare - Ndlovu, Kundai Valentine (Midlands State University, 2017)
The 1954 Hague Convention identifies art as part of the world’s irreplaceable cultural heritage which the world should cautiously safeguard to maintain our common identity. We sure cannot afford to lose such form of cultural heritage thus security in institutions like art galleries that have a responsibility for safe keeping art collections on behalf of the society should be taken seriously. In other words security should play a more meaningful role in care and preservation of art collections that is appropriate and effective in safeguarding artworks. Major research questions of the study included which security threats are being faced by First Floor Gallery? Which security measures are in place at the gallery? What can be done for effective safeguarding of collections? In this study qualitative research and an applied research design were employed. Through this research I realized that First Floor Gallery is facing a lot of challenges that are hindering the organization from adopting a security stance that is more effective in safeguarding of artworks. Also awareness of security risk and security risk management procedures should be enhanced in the organization to foster organizational participation in safeguarding art collections. Therefore First Floor Gallery Harare needs to make effort to overcome these challenges for it to not only stop unnecessary loss of artistic material but to be considered committed to the responsibility of safeguarding art collections on behalf of the society.